Estudio de prefactibilidad para la instalación de una planta procesadora de pasta de cebolla roja y ajo para base de aderezos en Lima-Metropolitana - Obregón Huamanchumo, Patricia Felícita (2018)
The present study will develop an investigation into the installation of a red onion and garlic paste processing plant for dressing base. It is worth mentioning that this work considers the study of demand, plant location, plant size, project engineering and financial economic evaluation.